Pemanfaatan Minyak Kemangi (Ocimum sanctum L) Sebagai Repellent Elektrik Lalat Rumah (Musca domestica) - Regita Ika Yasmin; Sardjito Eko Windarso; Rizki Amalia (Sanitasi: Jurnal Kesehatan Lingkungan, 2021)
One effort of vector control for reducing house flies (Musca domestica) density is by using basil oil as an electric repellent. The purposes of this research were to find out the effect of basil oil at 12 %, 15 %, and 18 % concentration on house fly density, and to identify the most effective con-centration. The study was a quasi experiment with pre-test and post-test with control group design, at four food stalls in 15 replications. The fly density was measured by using blockgrill with standard measurement procedure. The results showed that 12 % concentration of basil oil is able to reduce house fly density in average of 22,7 %, meanwhile the 15 % and 18 % concen-tration were able to reduce 54,3 %, and 89,5 %, respectively. Data analysis with Kruskal Wallis test at level of significance 95 % obtained a p-value <0,001; which can be concluded that the dif-ferences are statistically significant, or it can be interpreted that the different concentrations of basil oil as an electrical repellent affect the density of house flies. The most effective concentra-tion is 18%.